2009
DOI: 10.3109/07434610903384529
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Augmentative and Alternative Communication Methods with Infants and Toddlers with Disabilities: A Research Review

Abstract: This review sought to determine the evidence base of augmentative and alternative communication (AAC) use with infants and toddlers with disabilities. The review identified 12 studies, involving 190 participants aged 36 months or younger. The majority of the studies investigated unaided AAC methods (e.g., gestures or sign language), with 42% of the studies also including aided AAC methods. Although all studies reported improvement in child communication following AAC intervention, in-depth analyses of study me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(56 citation statements)
references
References 29 publications
1
52
0
3
Order By: Relevance
“…This research has established empirical evidence of the positive impact of AAC (Beukelman et al, 2007;Bopp, Brown, & Mirenda, 2004;Branson & Demchak, 2009;Fried-Oken et al, 2012;Ganz et al, 2011;Machalicek et al, 2010;Roche et al, 2014;Schlosser, Sigafoos, & Koul, 2009;Walker & Snell, 2013;Wendt, 2009) and has demonstrated that these gains come at no risk to speech development or recovery (e.g., Millar, Light, & Schlosser, 2006;Romski et al, 2010). As a fi eld, we should take pride in this increased research base that has resulted in advances in evidence-based AAC services.…”
Section: Research To Advance Understanding Of Communicative Competencementioning
confidence: 99%
“…This research has established empirical evidence of the positive impact of AAC (Beukelman et al, 2007;Bopp, Brown, & Mirenda, 2004;Branson & Demchak, 2009;Fried-Oken et al, 2012;Ganz et al, 2011;Machalicek et al, 2010;Roche et al, 2014;Schlosser, Sigafoos, & Koul, 2009;Walker & Snell, 2013;Wendt, 2009) and has demonstrated that these gains come at no risk to speech development or recovery (e.g., Millar, Light, & Schlosser, 2006;Romski et al, 2010). As a fi eld, we should take pride in this increased research base that has resulted in advances in evidence-based AAC services.…”
Section: Research To Advance Understanding Of Communicative Competencementioning
confidence: 99%
“…Moreover, there is evidence that AAC interventions pose no risk to speech development or recovery (e.g., Beukelman & Mirenda, 2013;Millar, Light, & Schlosser, 2006;Schlosser & Wendt, 2008). In addition, the myth of prerequisites to AAC intervention has been debunked, as the positive benefits of AAC have been demonstrated with infants and toddlers (e.g., Branson & Demchak, 2009;Light & Drager, 2012;Romski, et al, 2010) as well as with older beginning communicators with severe disabilities (e.g., Snell et al, 2010).…”
Section: Increased Awareness and Acceptance Of Aacmentioning
confidence: 99%
“…Over the past 30-40 years, there have been substantial changes to these practices. There is now a growing body of empirical evidence documenting the positive outcomes of AAC intervention (e.g., Beukelman, Fager, Ball, & Dietz, 2007;Bopp, Brown, & Mirenda, 2004;Branson & Demchak, 2009;Fried-Oken, Beukelman, & Hux, 2012;ganz, et al, 2011;Machalicek et al, 2010;Schlosser, Sigafoos, & Koul, 2009;Wendt, 2009). Moreover, there is evidence that AAC interventions pose no risk to speech development or recovery (e.g., Beukelman & Mirenda, 2013;Millar, Light, & Schlosser, 2006;Schlosser & Wendt, 2008).…”
Section: Increased Awareness and Acceptance Of Aacmentioning
confidence: 99%
See 2 more Smart Citations